Comparasion of gasoline additives and results in improved performance and fuel economy - Bolat R.M. (Modern Scientific Technology, 2024)
This study investigates the effects of various fuel additives on harmful emissions, fuel dynamics, and fuel efficiency, employing an observational research method. The materials used include base gasoline (G92) with the following additives in specified proportions: 15% isopropyl ether (G92-1), 1.5% aniline (G92-2), 1.5% diethylamine (G92-3), 3% dimethyl malonate (G92-4), and 3% p-tert-butylphenol (G92-5). This research aims to provide novel insights into the impact of these additives on fuel properties and emission reduction. Tests demonstrated that using additives could enhance engine power and dynamic performance, particularly with isopropyl ether. Additionally, additives impacted vehicle acceleration and fuel economy, with diethylamine showing the greatest efficiency. However, further research, especially under real-world conditions, is needed to confirm these findings and support broader application of these additives. It is also essential to consider other aspects, such as fuel lubricity and engine component durability, to provide a more comprehensive evaluation of the long-term effects of these additives.